Hungarian polymath Matthias Bel (1684–1749): crossing the boundaries of interpretation of his work in the modern Slovak historiography - Jablonský, Dávid; Součková, Taťána (Études sur la Région Méditerranéenne, 2023)
Matthias Bel, as one of the most influential Hungarian polymath, scholar, teacher and evangelical priest of the 18th century, was a big inspiration not only for Hungarian scholars and historiography, but also for the Slovak academic milieu. Following the example of leading European scholars, his rich scientific, pedagogical and spiritual career predestined him to compile a historical-geographical description of Hungary in the form of a multivolume work called Notitia Hungariae Novae historico-geographica, which even more than two centuries after its creation offers a rich information base for a wide range of Hungarian and Slovak academics. The paper reflects Matthias Bel’s work in the Slovak historiography of the second half of the 20th century and also new trends in research of his legacy at the beginning of the 21st century.